High-fidelity device for online recording of foot-stretcher forces during rowing - Krumm, D.; Simnacher, M.; Rauter, G.; Brunschweiler, A.; Odenwald, S.; Riener, R.; Wolf, P. (Procedia Engineering, 2010)
Foot-stretcher forces have been identified as key variables determining rowing performance. The aim of this study was to develop an instrumented foot-stretcher. Under each forefoot, a six degrees of freedom sensor was mounted on an adjustable frame. Under each rearfoot, a one degree of freedom sensor was placed. Validation resulted in an accuracy of vertical forces of about 1% full scale. Sensor's crosstalk was up to 11% of vertical load. The instrumented foot-stretcher was integrated into a high-level rowing simulator. Propulsive foot-stretcher forces were displayed online and could be used as concurrent feedback about rowing performance.